Poultry value chains and HPAI in Ethiopia - Ayele, G.; Rich, Karl M. (International Food Policy Research Institute, 2010)
The Ethiopian poultry sector is almost exclusively dominated by backyard and small-scale production using limited to no inputs in production and which is targeted for either self-consumption or the market. Unlike other parts of the world, there are relatively few intermediaries operating between producers and consumers in the Ethiopian poultry sector. However, because of increased urban development, there are newly emerging private farms responding to growing consumer demand. Indeed, rising demand for meat products has led to inflationary pressures on prices, with poultry prices increasing fivefold in nominal terms over the past decade. Nonetheless, while growing, broiler meat production remains fairly low, with most consumers favoring traditional forms of poultry over processed products.